Future for small states : overcoming vulnerability (Commonwealth Secretariat LondonGB, 1997)
Identifies the characteristics which most shape the security concerns particularly those that render them vulnerable. Considers the economic environmental and geopolitical dimensions of small state security. Examines measures small states can take to improve their national capacity and international presence.
DC